From Tropical to Sub-Tropical: Prolonged Reproductive Activity of the Invasive Ascidian Microcosmus exasperatus in the Eastern Mediterranean - Raijman Nagar, Lilach; Shenkar, Noa (Frontiers in Ecology and Evolution, 2016)
The solitary ascidian Microcosmus exasperatus is globally distributed in tropical and sub-tropical waters. In the Mediterranean it is considered an invasive species introduced through the Suez Canal, with a restricted distribution in the eastern basin. In order to understand the potential of this species to establish sustainable communities at additional sites in the Mediterranean, we studied its reproduction cycle over a 2-year period in relation to seawater temperature and chlorophyll-a data. Although M. exasperatus reproduces seasonally, with significantly greater activity in summer and early fall, mature oocytes occur throughout the year, suggesting multiple spawning periods. We found that reproductive effort significantly correlated with seawater temperature, while chlorophyll-a showed a low and insignificant explanatory power. A combined regression model of both parameters yielded the highest explained variance, suggesting a synergic effect of these two factors. Such a prolonged reproductive activity period enables repeated recruitment events. In view of the anticipated rise in seawater temperature, we predict that this species will gradually expand its distribution further across the Mediterranean.